Canticum B. Simeonis - Schütz, Heinrich,Spitta, Philipp (Breitkopf and Härtel, 1927)
1. Herr nun lässest du deinen Diener – 2. Herr nun lässest du deinen Diener
Full Score
Keywords: Sacred vocal music